ChemInform Abstract: Hexasulfanyl Analogues of Cyclotriveratrylene. Issue 39 (23rd September 2014) - Little, Marc A.; Loughrey, Jonathan J.; Santoro, Amedeo; Halcrow, Malcolm A.; Hardie, Michaele J.
Abstract Cyclotriveratrylene derivative (I) is prepared by tricyclomerization of the corresponding 3, 4‐disulfanylbenzyl alcohol derivatives in formic acid.